Acute Pancreatitis as a Complication of Antiepileptic Treatment: Case Series and Review of the Literature - Agnieszka Pawłowska-Kamieniak; Paulina Krawiec; Elżbieta Pac-Kożuchowska (Pediatric Reports, 2021)
Acute pancreatitis (AP) appears to be rare disease in childhood. In children, it has a different aetiology and course, and requires different management than in adult patients. The diagnosis of AP is based on at least two of the three criteria, which include typical clinical symptoms, abnormalities in laboratory tests and/or imaging studies of the pancreas. There are many known causes leading to AP in children including infections, blunt abdominal trauma, genetic factors, gallstone disease, metabolic disorders, anatomical defects of the pancreas, systemic diseases, as well as drugs, including antiepileptic drugs, and especially preparations of valproic acid. In our study, we present four cases of young patients diagnosed with acute pancreatitis as a complication of valproic acid therapy and we present a review of the literature. We believe that the activity of pancreatic enzymes should be monitored in children treated with valproate preparations in the case of clinical symptoms suggesting AP.